Association of polychlorinated biphenyls with vitamin D among rural Chinese adults with normal glycaemia and type 2 diabetes mellitus - Rui Zhang; Dandan Wei; Keliang Fan; Lulu Wang; Yu Song; Wenqian Huo; Qingqing Xu; Huadong Ni (BMC, 2024)
Abstract Background Endocrine function in patients with type 2 diabetes (T2DM) typically differs from those with normal glucose tolerance (NGT). However, few epidemiologic studies have explored how these differences impact the association between exposure to polychlorinated biphenyls (PCBs) and vitamin D levels. Methods This study included 1,705 subjects aged 18-79 years from the Henan Rural Cohort [887 NGT and 818 T2DM]. Linear regression was applied to evaluate the associations between PCB exposure and vitamin D levels. Quantile g-computation regression (QG) and Bayesian kernel machine regression (BKMR) were applied to evaluate the impact of PCB mixtures on vitamin D levels. Interaction effects of ΣPCBs with HOMA2-%β and HOMA2-IR on vitamin D levels were assessed. Results Plasma ΣPCBs was positively associated with 25(OH)D2 in the NGT group (β = 0.060, 95% CI: 0.028, 0.092). Conversely, in T2DM group, ΣPCBs was negatively associated with 25(OH)D3 and 25(OH)D (β = -0.049, 95% CI: -0.072, -0.026; β = -0.043, 95% CI: -0.063, -0.023). Similarly, both QG and BKMR analysis revealed a negative association between PCB mixture exposure and vitamin D levels in the T2DM group, contrary to the results observed in the NGT groups. Furthermore, the negative association of ΣPCBs with 25(OH)D2 and 25(OH)D disappeared or changed to a positive association with the increase of HOMA2-%β levels. Conclusions These findings suggest that decreased β cell function may exacerbate the negative effects of PCB exposure on vitamin D levels. Recognizing T2DM patients' sensitivity to PCBs is vital for protecting chronic disease health.